Community-Based Narcotics Prevention: An Effective Approach Towards Youth Drug Abuse Mitigation - Fransina S Latumahina; Anshari Betekeneng; Dandi Alvian Hakim; Arman Wally; Ari Fisal Waelissa (Indonesian Journal of Cultural and Community Development, 2023)
This study focuses on the escalating issue of narcotics misuse and its deleterious effects on health, families, and society, emphasizing the role of preventive socialization in addressing this crisis. Utilizing a community-based approach, Leihitu District KKN students implemented a "Drug Prevention Socialization" program, targeted at thirty local youths in Ureng Country. The objectives of this initiative were to enhance knowledge about the perils of drug addiction, foster resilience against drug involvement, and instigate motivation for drug prevention among these individuals. Through interactive counseling sessions, the program disseminated crucial information about the legal, health, and societal repercussions of narcotics abuse. Post-program assessments revealed a significant improvement in participants' understanding of drug misuse consequences and strategies to resist involvement. Thus, this study underscores the effectiveness of community-based drug prevention socialization in fostering informed and resistant youth populations, thereby contributing to wider efforts to combat the narcotics crisis.Highlights: Successful execution of the "Drug Prevention Socialization" program. Proven effectiveness of community-based prevention. Education-based approach fosters drug resistance. Keywords: Community-based Prevention, Narcotics Abuse, Youth Education, Drug Prevention Socialization, Substance Misuse